Historical blocking: MM 2021-02-23 to 2021-02-26 (Myanmar) - Voidly (2021)
CRITICAL severity censorship detected in Myanmar. Confidence: 86%. Data sourced from ooni-historical-backfill.
Censorship Incident ID: MM-2021-0032
Keywords: censorship; MM; censorship; critical